Soft System Methodology in Sustainable Destination Management : A Study of Andaman Islands in India - Manhas, Shalki (AMC Indian Journal of Entrepreneurship, 2020)
Tourism in island destinations needs extra planning and efforts to be economical, cultural, and environmental friendly as compared to mainland destinations. Sustainable tourism development is the key to this all-round approach towards tourism activities performed in the islands. This study aimed at identifying the economic, environmental, and social factors that are being affected due to development in tourism in the Andaman Islands, India by using the Soft System Methodology (SSM). The study involves assessing the challenges faced by the Andaman Islands, developing a conceptual model and implementing the model on ground for carrying out organized and sustainable entrepreneurship practices in these islands. The SSM approach is said to be successful in terms of reducing the negative impacts of any phenomenon and the implementation of this approach was rarely seen in the field of island destination management which was the major research gap found for the study. Using SSM, it was found that the administration of the islands lacked in practicing of cultural and environmental friendly tourism in the islands. The study also found that the major chunk of benefits go to foreign investors and not to local entrepreneurs. The study provides a better understanding of the impact of tourism on the island community and its environment, and measures to mitigate those impacts.